Software portability. - Lecarme, Olivier (McGraw-Hill, Inc., 1986)
"A much-needed text that presents for the first time the essential theory, methods, and techniques needed to understand and achieve successful software portability. A professional reference tool and an authoritative teaching manual designed to give software developers, amateur and professional programmers, and computer science students the capability to. • Evaluate the portability of various software products using more precise and uniform criteria • Select the most effective method for implementing new portable software. • Develop a program that meets current job requirements and is capable of being transported to a different system for future projects. • Cut the cost of new software development and increase the life span of a program's effectiveness. • Produce software that provides for more efficient use and greater range of applicability. • Investigate promising new areas of software portability." (Copied from the back cover).